First National Conference on New Health Practitioners - USAF School of Health Care Sciences (1972)
Internal memorandum written by Colonel Nicholas C. Nicholas, USAF on October 31, 1972 listing actions accomplished, meeting scheduled and planning and coordination needing to be accomplished (with dates) to prepare for the Physician Assistant Conference to be held at Sheppard Air Force Base, Texas in April 1973. A proposed agenda is attached titled "Fifth Annual Conference" as a continuum of the four conferences held at Duke University between 1968 and 1972. A paper by Dr. Edmund Pellegrino, the keynote speaker, is attached along with "my suggestions" for the conference - but it is unclear who authored the suggestions.